How Inclusive Is Abenomics? - Aoyagi, Chie (IMF Working Papers; Working Paper ;, 2015)
We assess the ongoing reform efforts in Japan in terms of inclusive growth. We use prefectural level panel data to regress a measure of inclusive growth, which incorporates both average income growth and income inequality, on macroeconomic and policy variables. Our analysis suggests that achieving the Bank of Japan's 2 percent inflation target has a positive effect on average income growth, but an adverse effect on income equality. The package of structural reforms planned under Abenomics is found to be effective in increasing both average income growth and income equality. The main policy implication of our analysis is that full implementation of structural reforms- especially labor market reforms-is necessary to both foster growth and increase equality.